A MODEL OF RELIGIOUS MODERATION EDUCATION IN MUHAMMADIYAH GENDING HIGH SCHOOL, PROBOLINGGO - Fazdilah, Ana; Ni'mah, Mamluatun; Zaini, Bahruddin (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to examine the educational model implemented by SMP Muhammadiyah Gending Probolinggo in instilling religious moderation values in students. Religious moderation is a vital principle in fostering a harmonious social life within Indonesia's diverse society. This research employs a qualitative case study approach, with data collection techniques including interviews, observation, and documentation. The findings reveal that the school develops an integrative religious moderation education model through curriculum integration, school culture, teacher role modeling, and extracurricular activities. The core values taught include tawassuth (moderation), tasamuh (tolerance), i'tidal (justice), musawah (equality), shura (deliberation), and tahadhdhur (civility). The implementation of this model is supported by participatory learning strategies, community involvement, and evaluation methods such as attitude observation, social projects, and student self-reflection. However, challenges such as social resistance, the influence of digital radicalism, limited teacher capacity, and the lack of contextualized materials present obstacles that need to be addressed. The study recommends strengthening teacher training, promoting multi-stakeholder collaboration, and developing learning materials based on local wisdom as strategic steps to optimize religious moderation education.